Marine waste management indicators in a tourism environment: exploring possibilities for Semporna District, Sabah - Prabakharan, Sudesh; Nair, Vikneswaran; Ramachandran, Sridar (Emerald Group Publishing, 2013)
Purpose: The aim of this paper is to examine the various indicators of marine waste management and its adaptability to the tourism industry in Semporna District, Sabah. Marine waste management was identified as a serious concern in Semporna, specifically the increase in general and hazardous waste and the lack of waste reduction activities. Selected waste management indicators can help to support information-based decision making in many levels of tourism planning and management. Design/methodology/approach: The paper is a critical review of previous studies. It provides a theoretical understanding for readers to recognize the indicators used in marine waste management in the context of managing the environment in tourism destinations. Findings: This paper provides an overview of the environmental indicators widely used in waste management of marine and island destinations and identifies indicators with potential for application in Semporna and islands off the coast of Semporna. Practical implications: The paper provides vital information to assist the local government select suitable indicators to alleviate marine waste management in Semporna, Sabah. Originality/value: The paper contributes to a better understanding of marine waste available management indicators in the tourism environment. The use of these dependable measurements should serve as a "report card" for each marine tourism site in the country.